2014
DOI: 10.1371/journal.pone.0109844
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the AbrA1/A2 Two-Component System in Streptomyces coelicolor and the Potential of Its Deletion Strain as a Heterologous Host for Antibiotic Production

Abstract: The Two-Component System (TCS) AbrA1/A2 from Streptomyces coelicolor M145 is a negative regulator of antibiotic production and morphological differentiation. In this work we show that it is able to auto-regulate its expression, exerting a positive induction of its own operon promoter, and that its activation is dependent on the presence of iron. The overexpression of the abrA2 response regulator (RR) gene in the mutant ΔabrA1/A2 results in a toxic phenotype. The reason is an excess of phosphorylated AbrA2, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…coelicolor is that iron de6represses the pleiotropic TCS, AbrA1/A2, which negatively regulates Act and Red production, although the mechanism has not yet been resolved 237 .…”
Section: The Impact Of Metals On Secondary Metabolismmentioning
confidence: 99%
“…coelicolor is that iron de6represses the pleiotropic TCS, AbrA1/A2, which negatively regulates Act and Red production, although the mechanism has not yet been resolved 237 .…”
Section: The Impact Of Metals On Secondary Metabolismmentioning
confidence: 99%
“…Yepes et al identified arbA1/A2 encoding a pleiotropic repressor of antibiotic production in S. coelicolor (Yepes et al, 2011). The deletion of arbA1/A2 in M145 (ΔabrA) not only enhanced the production of endogenous antibiotics such as ACT, RED and CDA, but also foreign NPs; the expression of the entire oviedomycin pathway derived from S. antibiotics ATCC 11891 in the ΔabrA mutant duplicated oviedomycin production as compared to the parent host M145 (Rico et al, 2014). Interestingly, expression of a pSET152 construct containing only 12 structural genes controlled by a single hrdB promoter in S. coelicolor M1146 also produced oviedomycin (Xu et al, 2017b).…”
Section: Streptomyces Coelicolor As a Heterologous Hostmentioning
confidence: 99%
“…Nevertheless, the signals that activate the different Streptomyces' TCS remain mostly unknown and just a few of them have been described to date (Figure 1D ). As an example, in S. coelicolor phosphate is the signal triggering PhoP/R (Sola-Landa et al, 2003 ), nitrogen balance seems to be related with AfsQ (Shu et al, 2009 ) and DraR/K (Yu et al, 2012 ) regulation, the level of iron seems to be the signal activating AbrA1/2 activator (Rico et al, 2014 ) and the presence of heme-oxidative stress provokes SenS/R reaction (Bogel et al, 2007 ; Ortiz de Orue Lucana and Groves, 2009 ). Most of the signals sensed by the TCS present in the genome of the Streptomyces spp.…”
Section: Studying Bacterial Sensors To Find Key Molecules Triggering mentioning
confidence: 99%